Penerapan Metode OCRA Dalam Menentukan Aplikasi Investasi Online Terbaik Dengan Menerapakan Pembobotan ROC - Dewi Maulida Sari Tanjung; Susi Mardiana Giawa; Miko Putra Haposan Tinambunan; Dito Putro Utomo (STMIK Budi Darma, 2022)
I the current era of development,tecgnology is increasingly sophisticated,one of wich is investing online.Online Investing applications or olso called online platforms are appliactions that investors use to invest with the aim of getting future profits th are carried out line anytime and anywhere.There are many types of investment apliactions that develop according to human needs.However, the lack of knowledge of the community or investor in choosing the best investment, namely,a system that will solve these problems using the OCRA method(Operational Competitivieness Rtaing) and ROC (Rank Order Centroid) wich produces the best decision based on predetermined criteria and data ,so that the conclusion is that best online investment application is OVO Invest in alternative A3 with a score 1.568.